2021
DOI: 10.3390/ijerph18136774
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Autism Spectrum Disorder (ASD) Etiology among Parents of Children with ASD

Abstract: Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social communication deficits and restricted or repetitive behaviors. Parental perceptions of the etiology of their child’s ASD can affect provider–client relationships, bonding between parents and their children, and the prognosis, treatment, and management of children with ASD. Thus, this study sought to examine the perceptions of ASD etiology of parents of children with ASD. Methods: Forty-two parents of children di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The three groups were optimistic about the effects of interventions, but the public needs to recognize that the effects of interventions on some autistic children are not always good. Some studies have shown that understanding the etiology and prognosis of autism may be more helpful for parents to support their autistic children ( 36 ), which suggests that we should teach parents more current scientific knowledge about autism as this can guide them to choose proper treatment methods and build their confidence in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The three groups were optimistic about the effects of interventions, but the public needs to recognize that the effects of interventions on some autistic children are not always good. Some studies have shown that understanding the etiology and prognosis of autism may be more helpful for parents to support their autistic children ( 36 ), which suggests that we should teach parents more current scientific knowledge about autism as this can guide them to choose proper treatment methods and build their confidence in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%